Optimising immunisations in early years – a shared partnership. (24th May 2012) - Beckmann, J; Banerjee, I
Abstract : The UK Childhood Immunisation Programme is vital to an effective Preventative Child Health Service for the Early Years. Evidence-based guidelines (eg. 'Green Book') exist to equip Immunisation Practitioners on key practices and vaccination policies. A review of referrals to our Paediatric Immunisation Clinic in a District General Hospital was undertaken to assess for trend in Primary Care referral patterns for immunisation queries, analyse the quality of referrals, and identify areas for improvement to local practice. All referrals made between March 2007 - February 2011 were retrospectively reviewed, including replying correspondence and hospital immunisation records. The reasons for referral, role of the referring healthcare professional, advice given by the attending clinician and details of hospital-supervised immunisations given were the main factors analysed. Data was compared in 12- and 24-month blocks to assess for trends in referral and outcome. 143 referrals were received. Main reason was to request for hospital-supervised immunisation in children with egg allergy - these referrals increased in number and proportion over time (7% in 2007-2008; 31% in 2010-2011). Comparatively fewer enquiries were regarding children with uncertain/incomplete immunisation status, timing of vaccination, or interrupted schedules following non-anaphylactic reactions to immunisations. Referrals were mainly from GPs (53%) and Practice nurses (37%). Thirty-five children (24%) received hospital-supervised immunisations - 54% received MMR vaccine. Overall, there was a decreasing trend in hospital-supervised immunisations (31% in 2007-9; 13.5% in 2009-11), particularly regarding referrals for egg or food allergies (71% in 2007-9; 0% in 2009-11), in line with recommended evidence-based guidelines. This review demonstrates the utility for a local Paediatric Immunisation Advisory Service in addressing local childhood immunisation enquiries, but with great effort from the clinicians involved. However, Paediatricians should not undermine their significant advisory, educational and public health promotion role in partnering with Primary Care to deliver a robust Childhood Vaccination programme. The increasing prevalence of food and egg allergies in children may require a reinforced Public Health message to address this knowledge gap in Primary Care, in order to increase parental acceptance and compliance for optimal uptake of immunisations in the community.